2012
DOI: 10.1186/1423-0127-19-96
|View full text |Cite
|
Sign up to set email alerts
|

Pro-life role for c-Jun N-terminal kinase and p38 mitogen-activated protein kinase at rostral ventrolateral medulla in experimental brain stem death

Abstract: BackgroundBased on an experimental brain stem death model, we demonstrated previously that activation of the mitogen-activated protein kinase kinase 1/2 (MEK1/2)/extracellular signal-regulated kinase 1/2 (ERK1/2)/ mitogen-activated protein kinase signal-interacting kinase 1/2 (MNK1/2) cascade plays a pro-life role in the rostral ventrolateral medulla (RVLM), the origin of a life-and-death signal detected from systemic arterial pressure, which sequentially increases (pro-life) and decreases (pro-death) to refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…MAPKs pathways are activated in response to a variety of extracellular and intracellular stimuli (15)(16)(17). Stimulation of MAPKs requires dual phosphorylation, which occurs as a consequence of sequential activation (18).…”
mentioning
confidence: 99%
“…MAPKs pathways are activated in response to a variety of extracellular and intracellular stimuli (15)(16)(17). Stimulation of MAPKs requires dual phosphorylation, which occurs as a consequence of sequential activation (18).…”
mentioning
confidence: 99%
“…Macrophages at an ischemic core region may present activated p38 MAPK, indicating that p38 MAPK may participate in the inflammatory responses when cerebral ischemic injury occurs (26). Activated p38 MAPK can enter into the cell nucleus or shift to other regions (27), and may further activate various transcription factors, including ATF-2/6, ATH-1/2, ETS21, MAX, HSF21, myocyte enhancer binding factor-22, nuclear transcription factor 2P, CHOP/GADD153, Elk-1 and SAP-1 (28). A study by Liu et al indicated that berberine reduces fibronectin and collagen accumulation through the p38 MAPK signaling pathway in rat glomerular mesangial cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 induction can also lead to upregulation of the COX-2/ PGE2 system in brain microvascular endothelial cells by activation of ETB-dependent MAPK cascades (Lin et al, 2013;Chuang et al, 2014). Based on a clinically relevant experimental model, it has been demonstrated that activation of both JNK and p38mapk in the rostral ventrolateral medulla sustains central cardiovascular regulation during progression towards brain stem death (Chang, 2012).…”
Section: Discussionmentioning
confidence: 99%